2005
DOI: 10.4140/tcp.n.2005.45
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Education in U.S. Schools of Pharmacy: A Snapshot

Abstract: Geriatric education in pharmacy schools has not increased proportionally with the expected increase in the geriatric population in the United States. Schools of pharmacy should make geriatric education a priority because the majority of patients whom pharmacists need to monitor or counsel currently are, and will continue to be, 65 years and older. Compared with a past study, the focus of current geriatrics education in pharmacy schools does not seem to have improved much despite the increasing need for geriatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Only 6 (14%) reported coursework in geriatrics as mandatory in the PharmD curriculum. 7 The most recent survey (2006) was conducted by the American Association of Colleges of Pharmacy (AACP) Geriatric Special Interest Group and was completed by 42% of the 89 US colleges and schools of pharmacy. The full results were not formally published but were summarized briefly by Odegard et al 8 Only 43% of respondents indicated that they had an elective geriatrics course.…”
Section: Enhancing Geriatric Competence Among Pharmacistsmentioning
confidence: 99%
“…Only 6 (14%) reported coursework in geriatrics as mandatory in the PharmD curriculum. 7 The most recent survey (2006) was conducted by the American Association of Colleges of Pharmacy (AACP) Geriatric Special Interest Group and was completed by 42% of the 89 US colleges and schools of pharmacy. The full results were not formally published but were summarized briefly by Odegard et al 8 Only 43% of respondents indicated that they had an elective geriatrics course.…”
Section: Enhancing Geriatric Competence Among Pharmacistsmentioning
confidence: 99%
“…202 Forty-two (50%) of the schools responded, and all of the respondents reported that they offered some type of course material in geriatrics for an average of 2 credit hours. Geriatrics was a required course in 14% of the colleges, integrated within another required course in 38%, and offered as an elective in 31%.…”
Section: Pharmacy Student Educationmentioning
confidence: 99%
“…201 In the 2003 survey, 57% of the faculty members responsible for teaching geriatrics reported having postgraduate training in geriatrics. 202 With the growing older adult population, it may be prudent for colleges to make required course work and faculty development in geriatrics a priority and to continue to strengthen the available advanced practice experiences. As an aid for course development and pharmacist professional development, ASCP has created the Geriatric Pharmacy Curriculum Guide.…”
Section: Pharmacy Student Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…While some colleges and schools of pharmacy included geriatric education in their curriculum, the extent of such training was not commensurate with the growing older population. 6 All pharmacy programs had practice experience options in geriatric or long-term care, but only 43% reported the option of an elective geriatrics course. 7 Although older individuals are the largest consumer group of prescription and nonprescription medications, 8 less than 1% of pharmacists have geriatric certification.…”
Section: Introductionmentioning
confidence: 99%